Pengaruh Pupuk Organik Cair terhadap Pertumbuhan dan Jumlah Daun Tanaman Kacang Panjang (Vigna sesquipedali) - Danga, Jeni Rambu Yaku; Bulu, Sesilia Irmaya; Riti, Dominggus Ngongo; Saghu, Yustina Sriyutun; Nduka, Restisary; Wohangara, Maria Gorety Landu; Lika, Rusnianti Rambu (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Liquid organic fertilizer (LOF) is increasingly utilized as an organic-based agricultural input to support environmentally sustainable crop production. The presence of nutrients in soluble form enables LOF to enhance vegetative growth during the early stages of plant development. This study assessed the vegetative response of long bean (Vigna unguiculata subsp. sesquipedalis) to LOF application using plant height and leaf number as growth parameters. The experiment was conducted from October to November 2025 at an agrotechnology practicum field characterized by relatively uniform environmental conditions. A Completely Randomized Design (CRD) was applied with three treatments, namely no LOF application, LOF at a rate of 20 mL per plant, and LOF at 40 mL per plant, each replicated three times. The collected data were analyzed using analysis of variance at a 5% significance level, followed by the Least Significant Difference test. The results revealed that different LOF application rates significantly affected vegetative growth of long bean plants. The application of LOF at 20 mL per plant resulted in the highest mean plant height (25.5 cm), which was significantly greater than that of the control (18.0 cm) and the 40 mL treatment (21.0 cm). A similar trend was observed for leaf number, where the 20 mL treatment consistently produced higher values than the other treatments. These findings indicate that LOF applied at a rate of 20 mL per plant is the most effective dosage for promoting early vegetative growth of long bean.